2001
DOI: 10.1080/136515001300374821
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis as an intervention in pain management: A brief review

Abstract: While there is a consensus that psychosocial factors play an important role in the experience of pain, clinical interventions for acute and chronic pain remain primarily biomedical. This pattern persists despite a body of recent empirical work supporting the effectiveness of a number of behavioral and relaxation interventions for these problems. One of these interventions is hypnosis. We briefly discuss hypnotic analgesia and describe how hypnosis can be integrated into biomedical treatment for acute and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The addition of post hypnotic suggestions has shown to decrease postoperative recovery time as well as pain perception and consumption of analgesics (Abdeshahi, 2013;Enqvist & Fischer, 1997;Mackey, 2010). This is in accordance with King et al (2001) systematic review concerning the use of hypnosis in pain management. This review regrouped a total of 38 studies assessing the effectiveness of hypnosis in relieving chronic pain, as well as pain and discomfort after a surgical procedure, and it investigates the difference between hypnosis, placebo and relaxation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The addition of post hypnotic suggestions has shown to decrease postoperative recovery time as well as pain perception and consumption of analgesics (Abdeshahi, 2013;Enqvist & Fischer, 1997;Mackey, 2010). This is in accordance with King et al (2001) systematic review concerning the use of hypnosis in pain management. This review regrouped a total of 38 studies assessing the effectiveness of hypnosis in relieving chronic pain, as well as pain and discomfort after a surgical procedure, and it investigates the difference between hypnosis, placebo and relaxation.…”
Section: Discussionsupporting
confidence: 78%
“…The results of this review indicated that hypnosis was always far superior in providing increased postoperative healing and in lessening the need for analgesics. King et al (2001) therefore concluded that hypnosis used as an adjunct to pharmacological means of pain alleviation could eventually lead to reduced consumption of medication. The present review concurs with this assertion, as all the studies evaluating postoperative analgesic consumption were in favour of hypnosis.…”
Section: Discussionmentioning
confidence: 99%